Effect of soil structure interaction on response of G+3 building - Varma, Maheswara; Sawant, V.A.; Chandaluri, V.K. (Journal of Structural Engineering, 2024)
In conventional analysis, superstructures are generally analysed considering their bases as either totally fixed or hinged. But in reality the superstructure, is connected to compressible soil-foundation system. Hence, there is a need of considering the compressibility of soil and flexibility of foundation for the analysis of superstructure. The effect of Soil-Structure Interaction (SSI) on a G+3 storey building frame with 2 bay resting on pile foundation is studied in the present paper wherein the pile foundations are embedded in Cohesive Soil. A FORTRAN 90 code is developed using three dimensional finite element method for the analysis to be more realistic. An uncoupled analysis is employed to demonstrate the effect of SSI. The results obtained by considering the effect of SSI are compared to that of building with fixed supports (neglecting underlying soil and foundation). A parametric study is conducted by varying pile length, pile diameter, pile spacing and configuration of the piles in the pile group along with the modulus of elasticity of soil. The effect of change in these parameters is observed by analysing the top displacements of the building frame as well as bending moments in both beams and columns. It is observed that these values have increased by a considerable factor when SSI is taken into consideration for the analysis.